2005
DOI: 10.1007/s11661-005-0070-y
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic damping characterization and microstructure evolution during high-temperature creep of an austenitic stainless steel

Abstract: We studied the microstructure evolution of an austenitic stainless steel, Type 316L, subjected to tensile creep at 973 K through the monitoring of shear-wave attenuation and velocity using electromagnetic acoustic resonance (EMAR). Contactless transduction based on the Lorentz force mechanism is the key to establishing a monitor for microstructural change in the bulk of metals with high sensitivity. In the short interval, 60 to 70 pct of the creep life, attenuation experiences a peak, independent of the applie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 43 publications
2
14
0
Order By: Relevance
“…[23][24][25][26][27][28] The results confirmed that an attenuation coefficient showed a peak at a specific time during the creep life and that the time does not depend on the stress and specimen shape.…”
Section: Introductionsupporting
confidence: 66%
See 3 more Smart Citations
“…[23][24][25][26][27][28] The results confirmed that an attenuation coefficient showed a peak at a specific time during the creep life and that the time does not depend on the stress and specimen shape.…”
Section: Introductionsupporting
confidence: 66%
“…As for 2.25 Cr-1Mo steel, Cr-Mo-V steel, Ni-based superalloy, and stainless steels, [23][24][25][26][27][28] the peak and minimum values of the attenuation and local minimum of the velocity were observed in the creep progression of quite different materials under the different test conditions. Shown in Table III is t/t r , where the attenuation shows the peak and the minimum in these materials.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Previously, we studied the relationship between the microstructure and ultrasonic properties, especially ultrasonic attenuation, with electromagnetic acoustic resonance (EMAR) [16][17][18] during creep in various metals. [19][20][21][22][23][24][25] EMAR is a contactless resonance method using an electromagnetic acoustic transducer (EMAT) [16][17][18] and developed for the contactless measurement of phase velocity and attenuation. The results confirmed that attenuation coefficient shows a peak at a specific time during the creep life and that time does not depend on stress.…”
Section: Introductionmentioning
confidence: 99%